Correlation and path analysis in Indian mustard (Brassica juncea L) for morpho-physiological traits in early maturing genotypes (Journal of Oilseed Brassica, 2026)
Thirty advanced progenies along with three check varieties of Indian mustard (Brassica juncea) were evaluated during Rabi 2019-20. The analysis of variance showed significant difference among genotype for all the characters. High estimate of heritability coupled genetic advance as percentage of mean was observed for 1000-seed weight, siliqua per plant and seed yield per plant. Medium heritability with medium genetic advance as percentage of mean was observed for water retention capacity of leaves, membrane stability index and secondary branches per plant. Correlation coefficient reflected that seed yield per plant showed positive and significant association with primary branches per plant (0.83), excised-leaf water loss (0.52), secondary branches per plant (0.52), siliqua per plant (0.44), days to 50 % flowering (0.35), main shoot length (0.32) and plant height (0.24). Path coefficient at genotypic level studied that secondary branches per plant (0.28), water retention capacity of leaves (0.21), main shoot length (0.19), excised-leaf water loss (0.15), days to maturity (0.09), primary branches per plant (0.08), siliqua per plant (0.07) had positive direct effect on seed yield per plant was observed. Thus, morphological and physiological characters confer the potentiality of particular genotype and association with yield is suitable for genotype selection.